2019
DOI: 10.1007/s10340-019-01156-y
|View full text |Cite
|
Sign up to set email alerts
|

Invasion history and management of Eucalyptus snout beetles in the Gonipterus scutellatus species complex

Abstract: Key message• The Eucalyptus snout beetle (ESB) continues to spread and impact Eucalyptus production worldwide  ESB has a confused taxonomic history and is known today to contain a number of cryptic species, which should be considered in management decisions. An integrated management approach is discussed for the future of ESB management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 104 publications
1
42
0
7
Order By: Relevance
“…Due to the nature of biological control and the specificity of the interaction between pest and biological control agent unidentified cryptic species, either the pest or biocontrol agent, could decrease the efficacy and success of the programmes (Bickford et al ., 2006). For example, the Eucalyptus weevil, Gonipterus scutellatus ( sensu lato ) has been a pest of Eucalyptus species for many years, with varying levels of control by a mymarid parasitoid, Anaphes nitens (Mapondera et al ., 2012; Schröder et al ., 2020). In the last decade, this weevil has reached pest status in Western Australia where it is also invasive (Mapondera et al ., 2012).…”
Section: Challenges In Dealing With the Identification Of Invasive Gamentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the nature of biological control and the specificity of the interaction between pest and biological control agent unidentified cryptic species, either the pest or biocontrol agent, could decrease the efficacy and success of the programmes (Bickford et al ., 2006). For example, the Eucalyptus weevil, Gonipterus scutellatus ( sensu lato ) has been a pest of Eucalyptus species for many years, with varying levels of control by a mymarid parasitoid, Anaphes nitens (Mapondera et al ., 2012; Schröder et al ., 2020). In the last decade, this weevil has reached pest status in Western Australia where it is also invasive (Mapondera et al ., 2012).…”
Section: Challenges In Dealing With the Identification Of Invasive Gamentioning
confidence: 99%
“…In the last decade, this weevil has reached pest status in Western Australia where it is also invasive (Mapondera et al ., 2012). Recent taxonomic studies suggested that the ineffectiveness of the parasitoid in some regions may be due to the presence of cryptic species in the pest genus (Mapondera et al ., 2012; Schröder et al ., 2020).…”
Section: Challenges In Dealing With the Identification Of Invasive Gamentioning
confidence: 99%
“…The eucalyptus snout beetle, Gonipterus sp. n. 2 (originally recorded as G. scutellatus) 41 , recorded in South Africa in 1916 (Figure 1), was the first serious non-native pest to affect non-native plantations in the country 42,43 . Numerous other non-native insect pests, especially those on Pinus spp.…”
Section: Non-native Insects and Fungimentioning
confidence: 99%
“…51 From the insect side, the eucalyptus snout beetle is at least in part responsible for the discontinued planting of Eucalyptus viminalis and E. globulus in the country. 40,42,43 And the recent introduction of the gall wasp L. invasa has already substantially influenced the Eucalyptus genotypes that can be planted in affected areas due to considerable differences in host resistance. 45,52 Much as in the case of introduced insect pests, a large number of host-specific pathogens of Pinus, Eucalyptus and Acacia species have been recorded in South Africa.…”
Section: Non-native Insects and Fungimentioning
confidence: 99%
See 1 more Smart Citation